2015
DOI: 10.1002/joc.4256
|View full text |Cite
|
Sign up to set email alerts
|

Meridional position biases of East Asian subtropical jet stream in CMIP5 models and their relationship with ocean model resolutions

Abstract: The East Asian subtropical jet (EASJ) stream in each of the 20 models from the Coupled Model Intercomparison Project Phase 5 (CMIP5) is evaluated against the ERA‐interim product. The multi‐model ensemble mean (MME) simulates a reasonably realistic climatology of the EASJ; however, the MME EASJs are shifted southward in all seasons in comparison with the observations. Upon closer inspection, it is found that only in the coupled general circulation models (CGCMs) with relatively coarse ocean model resolutions ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Furthermore, the CMIP6 models simulate smaller biases of U200 than the CMIP5 models (Figure 2(b,c)). The biases of U200 are characterized by a 'positivenegative-positive' tripole pattern, which is depicted by the shading in Figure 2(b), from south to north in the CMIP5 MME, which is similar to the results of Ma, Xu, and Lin (2015). The maximum and minimum biases are approximately 4.0 and −3.0 m s −1 , respectively.…”
Section: Methodssupporting
confidence: 66%
See 1 more Smart Citation
“…Furthermore, the CMIP6 models simulate smaller biases of U200 than the CMIP5 models (Figure 2(b,c)). The biases of U200 are characterized by a 'positivenegative-positive' tripole pattern, which is depicted by the shading in Figure 2(b), from south to north in the CMIP5 MME, which is similar to the results of Ma, Xu, and Lin (2015). The maximum and minimum biases are approximately 4.0 and −3.0 m s −1 , respectively.…”
Section: Methodssupporting
confidence: 66%
“…Based on 14 CMIP5 models, Huang et al (2013) reported that large differences existed in both the intensity and location of the simulated EAJ, which contributed to the uncertainty in the simulation of the EASR. Ma, Xu, and Lin (2015) also showed substantial meridional position biases for the EAJ among 20 CMIP5 models, although the multimodel ensemble (MME) was able to present a very realistic EAJ. Recently, Lin, Fu, and Lu (2019) also noted that the CMIP5 models exhibited large discrepancies in the longitudinal locations of the core of the EAJ.…”
Section: Introductionmentioning
confidence: 99%
“…To limit anthropogenic influence on climate systems, the 2015 Paris Agreement under the United Nations Framework Convention on Climate Change (UNFCCC) includes two long-term global temperature goals, i.e., "holding the increase in the global average temperature to well below 2 • C above pre-industrial levels and pursuing efforts to limit the temperature increase to 1.5 • C" (UNFCCC, 2015). While a world of 2 • C warming is inadequate to be considered safe (SED, 2015), there is a lack of scientific research regarding the 1.5 • C target, especially for regional climates (Mitchell et al, 2016). Studies generally evaluated differences of global climate impacts at global warming of 1.5 and 2 • C levels (Schleussner et al, 2016;Sanderson et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Associated with a positive phase of the SRP, high‐pressure anomalies over western Asia and East Asia and low‐pressure anomalies over Europe and central Asia, benefiting the precipitation over the northern Asia in summer, and vice versa for the negative phase of the SRP (Hong and Lu, ; Hong et al ., ; ; Wang et al ., ; Xuan et al ., ; He et al ., ). The SST variations over the eastern Pacific and the Indian Ocean would affect the precipitation variation over the eastern China by impacting the intensity of the EAJS (Zhang et al ., ; Kuang and Zhang, ; Lin and Lu, ; Huang et al ., ) or the meridional shift of the EAJS (Sampe et al ., ; Qu and Huang, ; Huang et al ., ; ; Ma et al ., ; Xue and Zhang, ).…”
Section: Introductionmentioning
confidence: 97%